Comparison of testicular development of hybrid crucian carp (Japanese white crucian carp ♀ × red crucian carp ♂) in traditional pond, lotus pond and rice paddy - Weiling Qin; Tao Dai; Jiamin Pi; Yuling Zhou; Yi Zhang; Siyang He; Xiaolong Zhou; Xiangyu Zhao; Qinqin Xiao; Huan Zhong; Yi Zhou (Reproduction and Breeding)
Traditional pond farming is the most important farming mode around the world. Recently, to develop ecological farming, lotus-fish and rice-fish co-culture modes have been widely used in southern China. However, the understanding of these ecological farming modes is insufficient. Preservation of fertility of fishes is crucial for maintenance of germplasm. In the present study, we focus on the testicular development in a widely farmed variety of crucian carp, hybrid crucian carp (Japanese white crucian carp ♀ × red crucian carp ♂, WR) in traditional pond (TP), lotus pond (LP) and rice paddy (RP). The fishes in the three groups had normal morphology of the testis. Analysis of the tissue sections suggested that LP group had higher content of spermatocytes and lower content of spermatids. The analysis of immunofluorescent markers of different cell types in testis indicated that all types of germ cells could be observed in the three groups while higher spermatocytes ratios were found in LP group. Comparison of steroid hormone levels in serum showed that the concentration of testosterone (T) was lowest in the RP group, while the concentration of luteinizing hormone (LH) was higher in the group LP than in the group TP. RNA-seq indicated that genes associated with meiosis and sperm formation tended to up-regulate both in the LP and RP group compared to the TP group. The qPCR results confirmed higher expression of nanog, gpr125, gfra1, dnd, ccna1, vasa, sox9a, and dmrt1 but lower expression of sycp3 in TP. These evidences suggested that the male hybrid crucian carp from the three modes were all fertile with different characteristics of spermatogenesis.